Toward understanding the redox properties of model chromophores from the greenfluorescent protein family: an interplay between conjugation, resonance stabilization, and solvent effects - Ghosh, Debashree; Acharya, Atanu; Tiwari, Subodh C.; Krylov, Anna I. (Journal of Physical Chemistry B, 2012)
The redox properties of model chromophores from the green fluorescent protein family are characterized computationally using density functional theory with a long-range corrected functional, the equation-of-motion coupled-cluster method, and implicit solvation models. The analysis of electron-donating abilities of the chromophores reveals an intricate interplay between the size of the chromophore, conjugation, resonance stabilization, presence of heteroatoms, and solvent effects. Our best estimates of the gas-phase vertical/adiabatic detachment energies of the deprotonated (i.e., anionic) model red, green, and blue chromophores are 3.27/3.15, 2.79/2.67, and 2.75/2.35 eV, respectively. Vertical/adiabatic ionization energies of the respective protonated (i.e., neutral) species are 7.64/7.35, 7.38/7.15, and 7.70/7.32 eV, respectively. The standard reduction potentials (E-red(0)) of the anionic (Chr(center dot)/Chr(-)) and neutral (Chr(+center dot)/Chr) model chromophores in acetonitrile are 0.34/1.40 V (red), 0.22/1.24 V (green), and -0.12/1.02 V (blue), suggesting, counterintuitively, that the red chromophore is more difficult to oxidize than the green and blue ones (in both neutral and deprotonated forms). The respective redox potentials in water follow a similar trend but are more positive than the acetonitrile values.